Analysis of MuluMile's Marketing Communication Strategy in Increasing Sales Volume - Mubarok, Muhammad Luthfi; Lestari, Mia; Nurfitriya, Mira; Rachmani, Nizza Nadya; Koeswandi, Tika Annisa Lestari (A Social Science and Entrepreneurship Journal, 2021)
This study aims to determine the marketing strategies used by MuluMile in increasing sales volume. This type of research is using a qualitative descriptive approach. The data analysis used is descriptive analysis, referring to the 4P concept of the marketing mix (Product, Price, Promotion, Place) and then SWOT analysis is used. Based on the analysis conducted, MuluMile has strategies in increasing sales volume, namely: 1) Products, a strategy used to improve product quality. 2) Price, providing affordable prices by reducing the level of profit of a product. 3) Promotion, making information media in social media (WhatsApp, Instagram and Facebook). 4) Place, give good service. Based on the internal and external analysis carried out at the MuluMile company, it can be found that MuluMile is currently in a development strategy. Where the decision to be taken is to develop the company by improving quality andcompleteness of the product and reproduce all forms of promotion.